Germ‐cell hub position in a heteropteran testis correlates with the sequence and location of spermatogenesis and production of elaborate sperm bundles. Issue 4 (3rd March 2015) - Ott, George J.; Shirkey, Nicholas J.; Haimo, Leah T.; Cardullo, Richard A.; Thaler, Catherine D.
SUMMARY In insects, spermatogonial cells undergo several mitotic divisions with incomplete cytokinesis, and then proceed through meiosis and spermatogenesis in synchrony. The cells derived from a single spermatogonial cell are referred to as a cyst. In the water strider Aquarius remigis, spermiogenesis occurs within two bi‐lobed testes. In contrast to most insects, in which the germ‐cell hub is located apically and sequential stages of spermatogenesis can be seen moving toward the base of the testis, each lobe of the water strider testis contains a single germ‐cell hub located medially opposite to the efferent duct of the lobe; the developing cysts are displaced toward the distal ends of the lobe as spermiogenesis proceeds. Water strider sperm have both a long flagellum and an unusually long acrosome. The water strider spermatids elongate most of the flagellum prior to morphogenesis of the acrosome, and exhibit several stages of nuclear remodeling before the final, mature sperm nucleus is formed. The maturing sperm are aligned in register in the cyst, and the flagella fold into a coiled bundle while their acrosomes form a rigid helical process that extends from the cyst toward the efferent duct. Mol. Reprod. Dev. 82: 295–304, 2015. © 2015 Wiley Periodicals, Inc.